The weeding practices of selected academic libraries in Metro Manila - Melgar, Sherryl Anne Jim A.; Ramos, Marian S. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2009)
Weeding is the practice of discarding, transferring to storage library materials that have excessive copies and that receive little or no usage at all (McGaw, 1956). Though academic libraries shares many problems and issues in deselecting resources, there are still variations in their withdrawal processes due to the different characteristics of the user community they serve and their goals (Evans and Saporano, 2005). In line with this, this study aimed to know the different weeding practices of selected academic libraries in Metro Manila.
The researcher was able to obtain survey responses from 32 head librarians of academic libraries that were members of the Philippine Association of Academic and Research Librarians (PAARL) from the year 2007 to 2008. Personal interviews with the head librarians of two selected libraries (Jose Rizal University and San Beda College) were also conducted for case studies that described the procedures involved in their individual weeding processes.
Data gathered from the survey and interviews revealed that: (a) majority of the respondents (93.3) weed their library collections; (b) the main objectives of academic libraries for weeding their collections is to remove obsolete material (92.6) and to open up more space (75); (c) case study subjects involve all members of the staff, working as a team, in collection evaluation and deselection; (d) the criteria commonly used in the per item evaluation of library collections by the two selected libraries include the material's physical condition, relevance to the programs offered by the educational institution they serve, usage, and availability of newer editions; (e) 19 (67.9 ) of the respondents weed their collections 'as the need arises'; (f) both case study respondents do not dispose all of the items they withdraw, they relocate some of the materials to an offsite or internal storage facility and donate some of it to other interested institutions; and, (g) the two interviewed library heads both claimed that they are satisfied with the present deselection practices, and that they do not encounter problems as long as they follow the policies concerned.
The researcher recommended for future similar studies to focus on both collection evaluation and withdrawal to better understand why libraries adopted their present weeding practices. By giving attention to evaluation, the study would be able to take into account other factors that are about the libraries themselves- the library staff, existing facilities, programs offered by the parent institutions, and the different characteristics of their clientele.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Academic libraries -- Philippines -- Manila Metropolitan Area; Discarding of books, periodicals, etc